Synthesis Dibenzyl Terephthalate Through Depolimerization of Poly (ethylene terephthalate) as Alternative of Waste Plastics Recycling - Suwardi, Suwardi; Partana, Crys Fajar; Salim, Agus; Anitasari, Dyah (Makara Journal of Technology, 2005)
Synthesis Dibenzyl Terephthalate Through Depolimerization of Poly(ethylene terephthalate) as Alternative of Waste Plastics Recycling. Synthesis dibenzyl terephathalate were done through PET degradation by refluxing in benzyl alcohol at 145oC temperature for 20, 24, and 28 hours in the presence of zinc acetate catalyst. The result of degradation was purified by recristalization in methanol and then melting point (mp), FTIR, 1H NMR spectra, and TLC spot were determined. The melting point of product degradation for 28 hours was 98-99 oC. Based FTIR spectra known that compunds of product degradation have OH, C=O, C-O, CH, monosubstituted benzene, disubstituted benzene groups, while on 1H NMR spectra showed chemical shift at 8.2 ppm (s, 10 H of monosubtituted benzene), 7.5 ppm (s, 9 H consist of 4 H disubstituted benzene and 5 H of aromatic benzyl alcohol), 5.4 ppm (s, 1 H from OH benzyl alcohol), 4.8 ppm (s, 4 H of methylene), and 2.9 ppm (s, 7 H of other traces). The single spot of TLC plate indicated that product degradation for 28 hours might be a single compund. Based these characterization concluded that compound of product degradation was dibenzyl terephthalate contains benzyl alcohol and other traces.